2012
DOI: 10.13171/mjc.2.1.2012.29.07.16
|View full text |Cite
|
Sign up to set email alerts
|

Highly diastereoselective synthesis of N-substituted 4-(diethoxyphosphoryl)-pyrrolidines-3-carboxylate starting from tetraethyl methylenediphosphonate

Abstract:  This paper describes a convenient synthesis of novel series of 3,4-disubstituted pyrrolidines based on the aza-Michael addition of primary amines to 3,4-difunctionalized-1,3-diene followed by an intramolecular cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Amri et al reported the use of this compound in the preparation of the diene 170 through a sequence that involves an alkylation with methyl bromoacetate and a Wittig–Horner reaction using formaldehyde (Scheme ). The diene 170 was subsequently used in the condensation with primary amines 171 to obtain a mixture of cis / trans 3,4-disubstituted pyrrolidines 172 in moderate to good yields, with the trans diastereoisomer being the major product …”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
See 1 more Smart Citation
“…Amri et al reported the use of this compound in the preparation of the diene 170 through a sequence that involves an alkylation with methyl bromoacetate and a Wittig–Horner reaction using formaldehyde (Scheme ). The diene 170 was subsequently used in the condensation with primary amines 171 to obtain a mixture of cis / trans 3,4-disubstituted pyrrolidines 172 in moderate to good yields, with the trans diastereoisomer being the major product …”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…The diene 170 was subsequently used in the condensation with primary amines 171 to obtain a mixture of cis/trans 3,4disubstituted pyrrolidines 172 in moderate to good yields, with the trans diastereoisomer being the major product. 142 To prepare 2,5-disubstituted pyrrolidines 174, Stahl ́s research group developed a Pd(II)-catalyzed oxidative cyclization of alkenes bearing tert-butanesulfinamide nucleophiles (173). 143 Even though they only reported one example using a phosphonylated alkene, it is important to note that only a single diastereomer was detected because of the presence of the sulfinyl group and the α-phosphonate near the nitrogen atom (Scheme 33).…”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…Previously, we have reported a new synthetic route to the diethyl (E)-1-(bromomethyl)-2-cyanovinylphosphonate 1 39 and its application in the synthesis of new vinylphosphonates 40,41 . Following our interest in the synthesis of polyfunctionalized 1,3-dienes [42][43][44] , we have sought to investigate, in the present work, the transformation of allyl bromide 1 into 1,3-dienes and the conditions of their preparation. For this purpose, we explored two ways which allow to obtain two families of 1,3-dienes 3 and 4 (Scheme 1), namely the use of allyl bromide 1 in an olefination type Wittig-Horner reaction (Route a) as well as its displacement using nitroalkane salts (route b).…”
Section: Introductionmentioning
confidence: 99%